¿Qué es ganar y qué es perder en política?: los retos en la participación electoral (2006)
Why do women succeed or fail in politics? This article seeks to answer that question in three stages. One, with reference to the formal regulations of electoral proceedings and their possible consequences for women’s participation. Two, women’s participation in politics in relation to the powerbrokers of political dynamics: ideological affiliation, the processes and criteria for internal nomination, and the resolve to place women in prominent positions on the electoral slates. Three, the obstacles, stumbling blocks, and opportunities that women who participate in politics encounter, deriving from traditional constructs of femininity (education level and professional advancement, distribution of family and domestic responsibilities).